Efficacy and safety evaluation of Allisartan Isoproxil in patients with hypertension: a meta-analysis - Zhao, Fengfeng; Liu, Yihua; Chen, Liang (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study aimed to evaluate the effectiveness and safety of Allisartan Isoproxil in the management of hypertension.: A comprehensive search was conducted across both English and Chinese databases, including the Cochrane Library, Embase, PubMed, Web of Science, CNKI, Wanfang Digital Periodical Full Text Database, and VIP Chinese Periodical Database (VIP), up to March 24, 2024. Randomized controlled trials (RCTs)investigating alisartan axetil for hypertension management were selected. Literature quality was assessed, and data were extracted for meta-analysis using Stata 15.1 software. The quality of evidence for outcome indicators was evaluated using the GRADE system level.Results: Six RCTs involving 767 participants were included. Meta-analysis revealed that, compared to placebo, the Allisartan Isoproxil group exhibited a significant reduction in systolic blood pressure (SBP) [WMD = -8.08, 95% CI (-11.81, 4.10), p = 0.000] and brachial-ankle pulse wave velocity (baPWV) [SMD = -0.69, 95% CI (-1.17, 0.20), p = 0.006]. However, the reduction in diastolic blood pressure (DBP) was not statistically significant [WMD = -5.48, 95% CI (-11.07, 0.10), p = 0.054]. Additionally, compared to calcium channel blockers (CCB) and angiotensin II receptor blockers (ARB), Allisartan Isoproxil did not significantly affect SBP [WMD = 0.20, 95% CI (-3.71, 4.10), p = 0.921] or DBP [WMD = 0.16, 95% CI (-2.11, 2.43), p = 0.891]. Allisartan Isoproxil demonstrated superior effects in increasing nitric oxide (NO) levels and decreasing endothelin (ET) levels compared to control groups [WMD = 9.56, 95% CI (6.42, 12.71), p = 0.000], [WMD = -7.42, 95% CI (-11.13, -3.71), p = 0.000], and showed a higher effective control rate of blood 2 pressure [RR = 1.26, 95% CI (1.13, 1.41), p = 0.000]. Subgroup analysis did not reveal significant differences. Regarding safety, there were no statistically significant differences in adverse events between the Allisartan Isoproxil group and the control groups [RR = 0.99, 95% CI (0.74, 1.32), p = 0.928], and no fatal adverse events were reported.Allisartan Isoproxil is effective in reducing SBP and baPWV, increasing NO, decreasing ET, and achieving a higher control rate of blood pressure in patients with essential hypertension. These benefits are achieved with minimal adverse reactions.